2019
DOI: 10.3348/kjr.2019.0407
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Cardiovascular Magnetic Resonance Imaging from the Korean Society of Cardiovascular Imaging—Part 2: Interpretation of Cine, Flow, and Angiography Data

Abstract: Cardiovascular magnetic resonance imaging (CMR) is expected to be increasingly used in Korea due to technological advances and the expanded national insurance coverage of CMR assessments. For improved patient care, proper acquisition of CMR images as well as their accurate interpretation by well-trained personnel are equally important. In response to the increased demand for CMR, the Korean Society of Cardiovascular Imaging (KOSCI) has issued interpretation guidelines in conjunction with the Korean Society of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Cardiac cine MRI consists of a movie loop at different cardiac time points, and it assesses the contraction and function of the cardiac chambers ( 11 ). Cardiac velocity encoding MRI (VENC-MRI) allows tracing of the velocity and direction of blood flow during a cardiac cycle ( 12 14 ). To the best of our knowledge, no studies have been conducted on the use of cardiac MRI for LAA emptying after catheter ablation of AF.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac cine MRI consists of a movie loop at different cardiac time points, and it assesses the contraction and function of the cardiac chambers ( 11 ). Cardiac velocity encoding MRI (VENC-MRI) allows tracing of the velocity and direction of blood flow during a cardiac cycle ( 12 14 ). To the best of our knowledge, no studies have been conducted on the use of cardiac MRI for LAA emptying after catheter ablation of AF.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, cardiovascular magnetic resonance (CMR) has emerged as a complementary tool for noninvasively evaluating AS [ 2 7 8 9 10 11 12 13 ]. Studies have shown its usefulness for the assessment of AVA and aortic hemodynamic parameters, either by planimetry of cine anatomical images or by analyzing velocity-encoded images using the continuity equation [ 14 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance (MR) contrast-enhanced myocardial perfusion imaging (MPI) can assess the extent and distribution of ischemia (1)(2)(3). In comparison to singlephoton emission CT or positron emission tomography, the established methods for clinical evaluation of myocardial perfusion, MR MPI offers superior spatial resolution with https://doi.org/10.3348/kjr.2019.0449…”
Section: Introductionmentioning
confidence: 99%